The Problem with Person‐Rearing Accounts of Moral Status. (15th May 2019) - Timmerman, Travis; Fischer, Bob
Abstract : Agnieszka Jaworska and Julie Tannenbaum recently developed the ingenious and novel person‐rearing account of moral status, which preserves the commonsense judgment that humans have a higher moral status than nonhuman animals. It aims to vindicate speciesist judgments while avoiding the problems typically associated with speciesist views. We argue, however, that there is good reason to reject person‐rearing views. Person‐rearing views have to be coupled with an account of flourishing, which will (according to Jaworska and Tannenbaum) be either a species norm or an intrinsic potential account of flourishing. As we show, however, person‐rearing accounts generate extremely implausible consequences when combined with the accounts of flourishing Jaworska and Tannenbaum need for the purposes of their view.